Innovative Cancer Survivorship Services for Rural and Underserved Communities. Issue 57 (3rd September 2021) - Argenbright, Keith; Berry, Emily
Abstract: In 2006, the Institute of Medicine recognized that cancer survivors faced complex physical and emotional health problems, often overlooked or inadequately managed. In Texas, access to programs specifically designed to address unique needs of cancer survivors is almost nonexistent for low-income uninsured or underinsured patients. In response to the unmet care needs of underserved cancer centers, Moncrief Cancer Institute, an affiliate of the National Cancer Institute–designated UT Southwestern Harold C. Simmons Comprehensive Cancer Center, established a community-based program using a survivorship care model similar to those offered in academic medical centers. Understanding that a one-size-fits-all approach could not successfully meet the needs across the service area, the cancer survivorship service line was mobilized to provide flexibility in delivery without sacrificing quality of care. The program continues to evolve, extending the foremost scientific information and resources into the communities it serves.